Magnetically Separable Humic Acid-Chitin Based Adsorbent as Pb(II) Uptake in Synthetic Wastewater - Ngatijo; Marlinda, Lenny; Malikhah, Wukhoidatul; Ishartono, Bayu; Basuki, Rahmat (Indonesian Journal of Chemical Studies, 2023)
Modification of humic acid (HA) from the peat soil of Jambi province, Indonesia with chitin and magnetite to form Fe3O4/HA-chitin has been successfully carried out. The successful synthesis was identified from characterization with functional group analysis, crystal analysis, magnetic strength measurement, and morphological and elemental analysis. The application of Fe3O4/HA-chitin to adsorb Pb(II) ion was analyzed using the Lagergren, Ho, Santosa, and RBS kinetics models (kinetics study) and the Langmuir, Freundlich, Dubinin-Radushkevich (DR), and Temkin isotherm model (isotherm study). The kinetics study followed the Ho model (pseudo-second order) with R2 and kHo of 0.9997 and 10264.59 g/mol min, respectively. The results of the data applicable to the Freundlich model showed that several sites were capable of multilayer adsorption (B) with a large enough adsorption capacity of 929.19 mg/g (about 28 times higher than the monolayer adsorption of Langmuir data). However, the outermost layer had a feeble adsorption energy of 0.51 kJ/mol, as measured by Temkin's adsorption energy. In the layer between the first layer (Langmuir) and the outermost layer (Freundlich), the DR isotherm was measured at a capacity of 104.87 mg/g (qD, the 3rd layer of the first layer) the adsorption energy was measured at 12.91 kJ/mol. A cross-study on the prediction of adsorption energy using the Santosa and RBS kinetics models showed that the RBS model had an adsorption energy value (26.45 kJ/mol) that was closer to the adsorption energy value of the Langmuir isotherm (27.55 kJ/mol).